Asphalt binder "Skincare"? aging evaluation of an asphalt binder modified by Nano-TiO2 - Lima, Orlando, Jr. (2022)
Aging by oxidation of asphalt roadway material promotes changes in its physical, chemical, and rheological properties, affecting its hardening and accelerating the degradation of its corresponding asphalt mixture. Titanium dioxide (TiO2) has been applied in engineering investigations to promote anti-aging and photocatalytic properties. In this study, a commercial binder was modified with nano-TiO2 (using contents of 0.1, 0.25, 0.5, 1, 2, 3, and 6%). It was evaluated by physicochemical and rheological tests (penetration, softening point, mass loss, dynamic viscosity, rheology, and Fourier transform infrared spectroscopy-FTIR) before and after aging by rolling thin-film oven test (RTFOT) and pressure aging vessel (PAV). The results indicated that incorporating nano-TiO2 mitigates binder aging, pointing out 0.25% as an optimum modification content for the investigated asphalt binder.